Mediating Role of Trust in Celebrity Endorsements and Millennial Purchases of Halal Tourism Packages - Nugraha, Aa Willy; Abdullah, Yusuf; Abdillah, Fitriyadi; Maulana, Lutfi (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2024)
The millennial generation is an active user of social media and is often exposed to promotional content from celebrities or influencers. While celebrity endorsements can increase exposure, not all endorsements are effective in driving purchase decisions. Thus, trust is the main factor that connects celebrity endorsements with purchase decisions. This research aimed to determine celebrity endorsement in improving the purchase of halal tourism packages and analyzing the mediation of trust in purchase decisions. This study used a quantitative survey method. The data analysis technique employed the Structural Equation Modeling method using purposive sampling. Respondents were selected based on age and social media users who made purchases of halal tour packages. The exclusion criteria included individuals who were only interested in or considering buying but had never traveled halal before, as they were not included as research respondents. The number of research samples was 130 participants. The study indicated that celebrity endorsers significantly influence millennial purchase decisions by mediating the trust variable on halal tourism packages. This study focuses on West Java millennials, limiting generalizability. Future research must expand to other regions and analyze the long-term trust effects that could enhance the understanding of halal tourism purchasing behavior. This finding contributed to halal tourism providers implementing effective marketing through social media optimization to encourage increasing sales.